Development of locally designed smart bike-sharing system on Thai campus: Lessons learnt of a pilot-scale study - Pakdeewanich, Chitsanu; Tiyarattanachai, Ronnachai; Anantavrasilp, Isara (My University, 2020)
Campus-wide bike-sharing program is one of the solutions for achieving sustainability in higher education. It also contributes to the UN's Sustainable Development Goals (SDGs). Smart bike-sharing systems have been implemented in some Thai cities and Thai universities since 2012. The systems were provided by foreign companies and developers. A locally designed smart bike-sharing system have been developed and pilot-scale tested at a Thai university. Many problems were found throughout the test-period, while design changes and application modifications were conducted to address the issues. The changes were done to make the system appropriate for the context of Thai university and users' demands. This paper discusses the development process and lessons learnt from this locally designed system. The results can be used by developers and software designers of bike-sharing industry to provide better design and implementation for Thailand market.
Keywords: Bike-sharing program; Sustainability; Sustainability in higher education